Selective Extraction of Metformin in Pharmaceutical Preparation via Synthesized MIP-SPE Techniqu - Kamal Aldeen, Rana Adnan; Al-Bayati, Yehya Kamal (Iraqi Journal of Science, 2023)
This work demonstrates the synthesis and storage of molecular-imprinted polymers (MIP) at room temperature using bulk polymerisation of Metformin (Met) characterized by high sensitivity, low cost, and high stability. To ensure an acceptable adsorption capacity, the research employed 0.8:4:20 mmol ratios of template, monomer, and cross-linking agents for the polymerization. A functional monomer, 2-acrylamido-2-methyl-1-propane sulphonic acid C7H13NO4S, was cross-linked with N,N-methylene bisacrylamide C7H10N2O2 to form Met-MIP, which could be characterized using a UV-VIS spectrophotometer at 236 nm, FT-IR spectroscopy, and scanning electron microscopy. The elution process that was applied to the template Metformin from the Met-MIP created cavities that were caused by the porogenic mixture solution of methanol, chloroform, and acetic acid (70:20:10, respectively). In accordance with the Freundlich isotherm model, Met-MIP had a maximum adsorption capacity of 5.2998 µmol/g and a template to monomer ratio of 1:2. A solid-phase extraction syringe packed with molecular imprinted polymers was used for the selective separation and pre-concentration of Metformin from aqueous solutions and estimation of Metformin by MIP and HPLC instruments in multiple pharmaceutical drugs of Metformin from several sources. The comparison with standard analytical techniques by MIP and RP-HPLC showed no significant difference between the two methods.